2022
DOI: 10.3390/ijerph19116460
|View full text |Cite
|
Sign up to set email alerts
|

Can Green Economy and Ecological Welfare Achieve Synergistic Development? The Perspective of the “Two Mountains” Theory

Abstract: China’s high-speed economic growth and severe environmental problems have resulted in a poor Environmental Performance Index and have affected China’s sustainable development and ecological welfare improvement. Therefore, exploring whether there is a certain relationship between the two and their influencing factors is an important way and a breakthrough to solve the problems regarding green economic progress and ecological welfare enhancement. To this end, by using the undesirable slack-based measure (SBM) mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 70 publications
1
9
0
Order By: Relevance
“…In fact, the evident spatial agglomeration and spatially correlated distribution of EWP require us to consider the spatial spillover effect in analyzing its changes and driving forces; otherwise, it will lead to biased analytical results. Ma et al [ 38 ] pointed out that industrial structure, urbanization and government regulation are conducive to improving the EWP, but the use of foreign capital will have a negative effect. The findings of this study confirm that these factors not only influence the EWP but also how it converges over time.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the evident spatial agglomeration and spatially correlated distribution of EWP require us to consider the spatial spillover effect in analyzing its changes and driving forces; otherwise, it will lead to biased analytical results. Ma et al [ 38 ] pointed out that industrial structure, urbanization and government regulation are conducive to improving the EWP, but the use of foreign capital will have a negative effect. The findings of this study confirm that these factors not only influence the EWP but also how it converges over time.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Xiao and Zhang discovered that urbanization and industrialization have significant negative spatial spillover effects on the EWP [ 37 ]. Ma et al found that urban growth, industrial structure and government investment have a promoting effect on the EWP, while foreign direct investment has an inhibitory effect [ 38 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…It indicates that economic development has beneficially promoted the reduction of CEI and has a spatial spillover effect on surrounding cities, showing that the carbon emissions per unit economy are significantly reduced, and the extensive economic development mode of the Yangtze River Economic Belt has been changing to intensive development and has entered the development stage on the right side of the Kunze curve. This may have something to do with the intensive green development guided by the government and the practice of the "Two Mountains Theory" (Ma et al, 2022a). The development of urbanization (the seventh line lnUdl) has beneficially promoted the reduction of CEI in the process of converting the rural population to the urban population, along with the further expansion of the urban scale and the further rationalization of the layout.…”
Section: Figurementioning
confidence: 99%
“…The index was proposed by Patrick Alfred Pierce Moran in 1950. The relevant formula is as follows (Ma et al, 2022a):…”
Section: Spatial Autocorrelation Analysismentioning
confidence: 99%